2007
DOI: 10.1158/0008-5472.can-06-4230
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement for DNAM-1, NKG2D, and NKp46 in the Natural Killer Cell-Mediated Killing of Myeloma Cells

Abstract: Recent evidence suggests a role for natural killer (NK) cells in the control of multiple myeloma. We show that expression of the NK cell receptor DNAM-1 (CD226) is reduced on CD56 dim NK cells from myeloma patients with active disease compared with patients in remission and healthy controls. This suggested that this receptor might play a role in NK-myeloma interactions. The DNAM-1 ligands Nectin-2 (CD112) and the poliovirus receptor (PVR; CD155) were expressed by most patient myeloma samples analyzed. NK killi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
258
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(277 citation statements)
references
References 20 publications
15
258
1
3
Order By: Relevance
“…Conversely, using the anti-CD96 NK92.39 mAb, we have not been able to point a role of CD96 in the lysis of Necl-5-expressing HCC cells by gd T effectors. Similarly, others groups did not succeed in demonstrating a contribution of CD96 to the NK-cell-mediated lysis of ovarian carcinoma or myeloma [27,29]. Our experiments indicate that Necl-5 but not Nectin-2 is involved in the DNAM-1-dependent recognition of tumor cells by gd T cells.…”
Section: Discussionsupporting
confidence: 64%
“…Conversely, using the anti-CD96 NK92.39 mAb, we have not been able to point a role of CD96 in the lysis of Necl-5-expressing HCC cells by gd T effectors. Similarly, others groups did not succeed in demonstrating a contribution of CD96 to the NK-cell-mediated lysis of ovarian carcinoma or myeloma [27,29]. Our experiments indicate that Necl-5 but not Nectin-2 is involved in the DNAM-1-dependent recognition of tumor cells by gd T cells.…”
Section: Discussionsupporting
confidence: 64%
“…Examples are the IgSF member DNAX accessory molecule-1 (DNAM-1)/CD226 and the CTLR NKp80 (Pende et al, 2006;Welte et al, 2006). DNAM-1 binds to adhesion molecules poliovirus receptor (PVR/CD155) and Nectin-2 (CD112) which also are IgSF members and broadly are expressed both by 'healthy' and malignant cells of epithelial and hematopoetic origin (Bottino et al, 2003;Pende et al, 2005;Carlsten et al, 2007;El Sherbiny et al, 2007). Engagement of DNAM-1 by these ligands was shown to substantially contribute to anti-tumour NK cytotoxicity (Pende et al, 2005(Pende et al, , 2006Tahara-Hanaoka et al, 2006;Carlsten et al, 2007;El Sherbiny et al, 2007).…”
Section: Activating Nk Receptors: Nk Cells' Alarm Systemmentioning
confidence: 99%
“…Since this receptor is of fundamental importance for the recognition and killing of several human tumors, including ovarian carcinoma (15)(16)(17)29), we next investigated the mechanism behind the modulation of DNAM-1 receptor expression in the tumor environment.…”
Section: Changes In 2b4 and Nkg2d Expression On Cd56 Dim Nk Cells Cormentioning
confidence: 99%
“…These studies provide the first direct evidence for a central role for DNAM-1 in tumor immune surveillance. DNAM-1 is important for NK cell-mediated recognition of several human tumors, including neuroblastoma, myeloma, and Ewing sarcoma (16,17,29,35). We have previously shown that the DNAM-1/CD155 interaction is crucial for the recognition of freshly isolated ovarian carcinoma by allogeneic NK cells (15).…”
Section: Tumor-associated Nk Cells Fail To Target Autologous Tumor Cementioning
confidence: 99%